Comparison of Egg Weight Between Two Quail Strains - Vali, Nasrollah; Edriss, M.A.; Moshtaghi, H. (International Journal of Poultry Science, 2006)
In order to investigate egg weight of two quail strains 2550 eggs of Japanese quail (Coturnix japanese) and 1975 eggs of Range quail (Coturnix ypisilophorus) were weighted individually at three age groups (first group: 60-145, second group: 145-230, and last group: 300-385 days of age). Body weights of two strains were not significantly different (p>0.05). Body weights at 60 days age were significantly different (p< 0.01), but there were not any significant difference between the ages of 145 and 300 days (p>0.05). Egg weight of Japanese quails and Range quails were 11.23±0.03 and 11.17±0.05 respectively which were not significantly different (p>0.05). Effects of the interaction of strain, age and sex for egg weight and body weight were significantly different (p< 0.01). Minimum and maximum egg weight for Japanese quail were 7.08 and 13.84gr respectively, however these records were 7.01 and 13.84gr for Range quail. Individual variation of in two strains for eggs weight were significantly different (p< 0.01).